Water-soluble polyphenol-rich clove extract lowers pre- and post-prandial blood glucose levels in healthy and prediabetic volunteers: an open label pilot study - Ratheesh Mohan; Svenia Jose; Johannah Mulakkal; Darla Karpinsky-Semper; Andrew G. Swick; I. M. Krishnakumar (BMC, 2019)
Abstract Background/objectives Type 2 diabetes (T2D) is a global pandemic, and contributes significantly to the increasing incidence of conditions such as cardiovascular disease (CVD). Postprandial plasma glucose measured 2-h after the start of a meal is a good indicator of the overall status of glucose homeostasis. Clove (Syzygium aromaticum L.) and its essential oils (eugenol and acetyl eugenol) have been shown in preclinical studies to modulate pathways involved in glucose homeostasis. In addition, a water-soluble polyphenolic extract of unopened clove buds was recently shown to benefit liver function and redox status. Therefore, we conducted an open-label pilot study to test whether this polyphenolic clove extract (PCE) could influence glucose metabolism. Methods We evaluated the effect of PCE supplementation (250 mg once daily for 30 days) on preprandial glucose levels and 2-h postprandial glucose levels in 13 otherwise healthy volunteers who were stratified into two groups according to their initial preprandial glucose levels: Group I (n = 7) ≤100 mg/dL, Group II (n = 6) - between 101 and 125 mg/dL. In an effort to elucidate the molecular mechanisms of PCE action, we tested in vitro the effects of PCE on glucose uptake, hepatocyte glucose production, and carbohydrate hydrolyzing enzymes. Results At day 12 of supplementation, we observed statistically significant reductions in mean postprandial glucose levels in both groups [(Group I: Initial - Day 12 PPG = 13.29 mg/dL, 95% CI: 3.329-23.24) (Group II: Initial - Day 12 PPG = 16.67 mg/dL, 95% CI: 4.687-28.65, P = 0.0159)], which continued through study completion at day 30. PCE supplementation significantly decreased mean preprandial glucose levels only in Group II at Days 24 (Initial - Day 24 = 13.00 mg/dL, 95% CI: 1.407-24.59, P = 0.0345) and 30 (Initial - Day 30 = 13.67 mg/dL, 95% CI: 5.766-21.57, P = 0.0067). In cell-based assays, PCE enhanced glucose uptake in L6 myocytes and inhibited hepatocyte glucose production HepG2 cells. In cell-free assays, PCE inhibited α-amylase activity and α-glucosidase activity. Conclusions These findings underscore the therapeutic utility of PCE for maintaining healthy glucose metabolism and warrant further larger-scale clinical trials. Trial registration This trial was retrospectively registered in the ISRCTN registry on September 29, 2018 (ISRCTN15680985).